UTILIZATION OF INTERNET-BASED LEARNING MEDIA IN ENHANCING SCIENCE LITERACY CAPABILITIES OF PGSD STUDENTS - Asep Samsudin; Jajang Bayu Kelana; Agni Muftianti (PrimaryEdu : Journal of Primary Education, 2019)
This study was to determine the effect of the use of internet-based learning media in improving the scientific literacy skills of PGSD students. The method used in this study was pre-experimental with the research design of one group pretest-posttest. The population in this study were all IKIP Siliwangi PGSD students in the fourth semester of regular classes and non-regular classes with a total of 300 students. The sample in the study was regular class students with 38 students. The instruments used included tests, validation sheets and observation sheets. Research results show that the sig value. (2-tailed) 0,000 <0,05, it can be concluded that H0 is rejected and H1 is accepted. Thus there is a difference in the average scientific literacy ability between pretest and posttest and it can be concluded that the use of internet-based learning media can improve students' scientific literacy skills. Student observation data shows that learning using internet-based learning media can increase student activity with the percentage of 53.75% of active students and 46.25% of fasive students in learning.